The effect of 5-week exercise program on oxidative stress and response to acute exercise among sedentary subjects - Farah Fauzi,; Siti Balkis Budin,; Shahrul Azwan,; Leong, Kok Yuen (penerbit ukm, 2007)
Physical training is associated with axidative stress and improvement in blood antioxidant status. In this study, we investigated the effects of training on plasma malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE) as markers of lipid peroxidation, superoxide dismutase (SOD) activity, and ascorbic acid (AA) after a single bout of acute exercise. Twelve healthy, untrained young adult men were recruited for 5 weeks of aerobic training period. They were subjected to a rope-skipping exercise for 20 minutes at the intensity of 65 – 80% of heart rate reserve, thrice weekly. They also had to perform a single, acute bout of the same exercise protocol prior to and after training period. Venous blood samples were collected at resting condition (BL), immediately (0 h) and 24 hours (24 h) post acute exercise on both single bout sessions. Results showed that the pattern changes of oxidative stress response are quite similar on both acute sessions. The acute bouts of rope-skipping is associated with a significant increased (p= 0.001) in lipid peroxidation markers immediately after cessation of exercise, with a concomitant increase in antioxidant levels, albeit higher when compared to pre-training values (p = 0.001). These changes were followed by a significant decreased (p = 0.001) in all parameters, toward resting values, 24 hours thereafter. The training program seemed to induce a significant increase in MDA and 4-HNE but also enhanced the antioxidant defense system namely SOD and AA among the untrained subjects.